A Community-transmitted Case of Severe Acute Respiratory Distress Syndrome (SARS) Due to SARS-CoV-2 in the United States. (30th March 2020) - Sanville, Bradley; Corbett, Rebecca; Pidcock, Wesley; Hardin, Kaitlyn; Sebat, Christian; Nguyen, Minh-Vu; Thompson, George R; Haczku, Angela; Schivo, Michael; Cohen, Stuart
Abstract: This is the first known community transmission case of the novel coronavirus disease (COVID-19) in the United States, with significant public health implications. Diagnosis of COVID-19 is currently confirmed with PCR based testing of appropriate respiratory samples. Given the absence of travel or known exposure history, this patient did not meet the criteria for testing according to CDC guidelines at the time of her presentation. Since this case, any patient with severe disease (eg, ARDS or pneumonia) requiring hospitalization without an explanatory diagnosis can be tested even if no clear source of exposure is identified. While influencing national health policies for revising screening criteria, this case also highlighted significant knowledge gaps in diagnosis and treatment and a desperate need for early, widespread, fast and cheap testing for COVID-19.